Entry, exit and productivity. Empirical results for German manufacturing industries - Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2007)
Using panel data from Spain Farinas and Ruano (IJIO 2005) test three hypotheses from a model by Hopenhayn (Econometrica 1992): (H1) Firms that exit in year t were in t-1 less productive than firms that continue to produce in t. (H2) Firms that enter in year t are less productive than incumbent firms in year t. (H3) Surviving firms from an entry cohort were more productive than non-surviving firms from this cohort in the start year. Results for Spain support all three hypotheses. This paper replicates the study using a unique newly available panel data sets for all manufacturing plants from Germany (1995 – 2002). Again, all three hypotheses are supported empirically.
Keywords: Productivity; Produktivität; 330 Wirtschaft